Clinical Application of CAD/CAM-Guided Modified Dautrey's Procedure in Recurrent Temporomandibular Joint Luxation. Issue 2 (30th March 2023) - Zhu, Taomin; Li, Chengfeng; Jia, Xueke; Li, Huimin; Feng, Yaping; Ke, Jin
Abstract : This study aimed to introduce the clinical application of the CAD/CAM-guided modified Dautrey's procedure in recurrent anterior temporomandibular joint luxation and evaluate its clinical effects. Four selected patients were treated by the CAD/CAM-guided modified Dautrey's procedure and were followed-up to access their curative effect. Joint pain and sound, recurrence rate, mandibular function, maximum mouth opening (MMO), symptoms of facial nerve injury, and changes in zygomatic facial appearance were observed in postoperative follow-up. The followed-up period ranged from 3 months to 1 year with an average time of 7.5 months. There was no recurrence in all 4 patients, and no symptoms of facial nerve injury and zygomaticofacial appearance changes were found. All patients showed improvement in MMO, with a mean preoperative and postoperative MMO of 4.74 and 3.74 cm, respectively. All of them showed relief of joint pain or sound 3 months or more after the operation and could exercise mandibular normally. This results showed that the CAD/CAM-guided modified Dautrey's procedure was effective in the treatment of recurrent temporomandibular joint luxation and could be used as a good alternative treatment for it.